A Self-Balancing 13-Level Single-Phase Triple Gain Inverter - Sakthisudhursun Balakrishnan; Muralidharan Srinivasan; Sundaramahalingam Subramaniam; Vanaja Narayanaswamy (Buletin Ilmiah Sarjana Teknik Elektro, 2026)
A potential single stage power electronics interface for integrating renewable sources like PV, fuel cells, etc. with an AC load is a switched capacitor based multilevel inverter with boosting capability. In this research, a thirteen-level MLI topology with voltage boosting factor of three a gain of three for the renewable energy integration is proposed. The proposed MLI requires twelve unidirectional switches, one bidirectional switch, three capacitors, and a single DC source. The voltage stress across each switch is lower than the peak output voltage since the proposed inverter doesn't need a back-end H-Bridge. The proper selection of switching sequence enables the self regulation of voltage across all three capacitors, is self-regulated eliminating the need of additional sensor/control. Simulation results obtained from MATLAB/Simulink confirm the stable operation of the MLI and the self-regulation of switched capacitor voltages under step variations in load, source voltage, and modulation index. A comprehensive comparison with existing topologies demonstrates the superiority of the proposed topology in terms of reduced total number of components and lower total blocking voltage.